Does Job Loss Make You Smoke and Gain Weight? - Jan Marcus (Economica, 2014)
This paper estimates the effect of involuntary job loss on smoking behaviour and body weight using German SOEP data. Baseline non-smokers are more likely to start smoking due to job loss, while smokers do not intensify smoking. In particular, single individuals and those with lower health or socioeconomic status prior to job loss exhibit high rates of smoking initiation. Job loss increases body weight slightly, but significantly. The applied regression-adjusted semiparametric difference-in-difference matching strategy is robust against selection on observables and time-invariant unobservables. This paper provides an indirect test that the identifying assumption is not violated.
Additional information: This is an electronic version of an Article published in Economica 81 (2014), 324, S. 626-648 at http://dx.doi.org/10.1111/ecca.12095
Keywords: I12; J65; 330; Job loss; smoking; health behavior; difference-in-difference; propensity score matching; Arbeit; Arbeitslosigkeit; Rauchen; Gesundheit